Pemberian Asam Humat Dan Bio-Nuklir Terhadap Pertumbuhan Dan Hasil Tanaman Padi (Oryza Sativa L.) Di Poktan Pranggang - Agus Fahmi; Yazid Bastomi (Fakultas Pertanian, Universitas Darul Ulum, 2026)
This study aimed to determine the effect of humic acid and Bio-Nuclear application on the growth and yield of rice (Oryza sativa L.) at Pranggang Farmer Group, Brambang Village, Diwek District, Jombang Regency. The research was conducted from January to April 2024 using a factorial randomized block design with two factors and three replications. The first factor was the dosage of humic acid consisting of H0 = without humic acid, H1 = 5 L ha-1, and H2 = 10 L ha-1. The second factor was the application of Bio-Nuclear consisting of B0 = without Bio-Nuclear, B1 = 5 mL L-1, and B2 = 10 mL L-1. Observed parameters included plant height, number of tillers, number of leaves, panicle length, number of filled grains, 1000-grain weight, and grain yield per hectare. Data were analyzed using analysis of variance (ANOVA) followed by Honestly Significant Difference (HSD) test at 5% significance level. The results showed that the application of humic acid and Bio-Nuclear significantly affected vegetative growth and rice yield. The H2B2 treatment combination produced the best results on plant height, productive tillers, and grain yield. Humic acid improved nutrient availability and soil physical properties, while Bio-Nuclear enhanced microbial activity and nutrient uptake efficiency. The combination of both treatments has the potential to increase rice productivity sustainably.